Recepcja myśli mariologicznej i maryjnej Johna Henry’ego Newmana w mariologii Soboru Watykańskiego II - Beyga, Paweł (Studia Europaea Gnesnensia, 2018)
The main goal of this article is to show how John Henry Newman’s Mariology and thought on Blessed Mary penetrated into the Mariology of the Second Vatican Council. To begin with, the author outlines the context of Newman’s theological activity as well as the context of the last Council. Subsequently, selected aspects of Newman’s mariological reflection are discussed as they emerge in the conciliar documents. The author then advances a theological assessment of Newman’s conceptions which found their way into the documents of the council.